2015
DOI: 10.3892/etm.2015.2562
|View full text |Cite
|
Sign up to set email alerts
|

Sodium houttuyfonate inhibits biofilm formation and alginate biosynthesis-associated gene expression in a clinical strain of Pseudomonas aeruginosa in vitro

Abstract: The increasing multidrug resistance of has become a serious public-health problem. In the present study, the inhibitory activities of sodium houttuyfonate (SH) against biofilm formation and alginate production in a clinical strain of (AH16) were investigated using crystal violet dying and standard curve methods, respectively. The cellular morphology of treated with SH was observed using a scanning electron microscope. Furthermore, reverse transcription-quantitative polymerase chain reaction was used to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Drug treatment was conducted as described above. Total RNA was isolated as previously described with some modifications [18,19]. Biofilms were dislodged by 1 mL TRIzon reagent of Ultrapure RNA Kit (CWBio, Beijing, China) and the suspension was collected.…”
Section: Methodsmentioning
confidence: 99%
“…Drug treatment was conducted as described above. Total RNA was isolated as previously described with some modifications [18,19]. Biofilms were dislodged by 1 mL TRIzon reagent of Ultrapure RNA Kit (CWBio, Beijing, China) and the suspension was collected.…”
Section: Methodsmentioning
confidence: 99%
“…SNH has spectrum wide antibacterial activity, few adverse reactions, and improves immunity ( Juanjuan, 2009 ; Yumei et al, 2012 ; Yang et al, 2016 ). Previously, we confirmed that sodium houttuyfonate (SH) has a certain inhibitory effect on P. aeruginosa ( Shao et al, 2013 ; Wu et al, 2014 ; Wu et al, 2015 ). SNH and SH structures are highly similar, but SNH is more chemically stable than does SH ( Yumei et al, 2012 ).…”
Section: Introductionmentioning
confidence: 63%
“…Recently, SH was found to inhibit the biofilm formation of P. aeruginosa, S. aureus, and C. albicans in vitro (20)(21)(22)(23)(24)(25), but the detail of mechanisms remains unclear. Previously, we found that SH in combination with erythromycin groups at sub-inhibitory concentrations could effectively inhibit the biofilm formation of S. epidermidis at adhesion and maturation stages (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our group found that SH is promising and effective at repressing pathogenic related biofilm formation and motility of Pseudomonas aeruginosa (20)(21)(22), and can inhibit S. epidermidis and Candida albicans (20,23), and act synergistically with Na 2 -EDTA and levofloxacin against biofilm formation of P. aeruginosa, S. aureus and C. albicans (23,24). In addition, we found that SH is a possible natural analog of N-acyl-homoserine lactone, and can effectively inhibit the Las quorum sensing (QS) system and regulated virulence factors of P. aeruginosa (25).…”
Section: Introductionmentioning
confidence: 99%